Warum blieb in der russischen Landwirtschaft die duale Struktur von Großbetrieb und Hauswirtschaften erhalten?; Why has the Dual Structure of Larger-scale Farms and Household Plots been Preserved in Russian Agriculture? - Eberhard Schulze (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– The collectivisation of agriculture in most socialistic countries was connected with the development of a dual enterprise structure of large-scale farms and household plots. In Russia, in contrast to other European transition countries, this structure in most regions remained in the main features. The article tried to find reasons for this development. It has been recognised that beside the macroeconomic situation above all the intersection of the three institutional and organisational systems large scale enterprise, rural community and household plots is of importance. Based on this, suggestions for continuation of the agrarian reform in Russia are derived.
Keywords: 330; Landwirtschaftlicher Familienbetrieb; Systemtransformation; Russland